2018
DOI: 10.3390/ijerph15122651
|View full text |Cite
|
Sign up to set email alerts
|

Migrant Farmworkers’ Exposure to Pesticides in Sonora, Mexico

Abstract: Expanding agribusiness in Sonora, a state in Northern Mexico, has increased the demand for temporary migrant agricultural workers. Sonora is one of the top states in Mexico for pesticide utilization. We conducted an exploratory study to evaluate exposure to organophosphate (OP) and pyrethroid pesticides among migrant farmworkers. A sample of 20 migrant farmworkers was recruited from a large commercial grape farm during the harvest season. We administered a questionnaire on work activities, exposure characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 47 publications
1
9
0
1
Order By: Relevance
“…While the sample size for the biological monitoring component of this study was relatively small, we did measure the highest exposures in samples collected during the agricultural spray season from women who reported mixing and applying pesticides. These outlying measurements were more than an order of magnitude higher than the 95th percentile of exposures measured in women and Mexican-Americans in the National Health and Nutrition Examination Survey [ 45 , 46 , 47 ], and notably higher for 3-PBA and trans -DCCA compared to the highest levels measured among migrant male farmworkers in Sonora, Mexico [ 48 ] (see Table 3 ). Further, the single highest exposure was measured in one such woman who reported that she never received any pesticide safety training.…”
Section: Discussionmentioning
confidence: 98%
“…While the sample size for the biological monitoring component of this study was relatively small, we did measure the highest exposures in samples collected during the agricultural spray season from women who reported mixing and applying pesticides. These outlying measurements were more than an order of magnitude higher than the 95th percentile of exposures measured in women and Mexican-Americans in the National Health and Nutrition Examination Survey [ 45 , 46 , 47 ], and notably higher for 3-PBA and trans -DCCA compared to the highest levels measured among migrant male farmworkers in Sonora, Mexico [ 48 ] (see Table 3 ). Further, the single highest exposure was measured in one such woman who reported that she never received any pesticide safety training.…”
Section: Discussionmentioning
confidence: 98%
“…Studies documenting the impacts or alterations in wildlife, persistence in the environment, or human health caused by glyphosate are abundant worldwide 20,21,66,67 . However, these side effects are not unique to glyphosate 68–71 . In addition, most studies were conducted using only the active ingredient, but not commercial formulations.…”
Section: Glyphosate Banmentioning
confidence: 99%
“…Inadequate pesticide storage is common among Mexican farmers and, most pesticide users do not have sufficient training to handle and dispose empty containers 25 . In hot climates like Mexico many users do not use personal protective equipment due to discomfort 70 . In addition, most pesticide users are unaware of the legislation regarding the use of pesticides because they do not receive visits from officials of the regulatory agencies, 24 such as COFEPRIS, the CESAVEs (Comités Estatales de Sanidad Vegetal) or SENASICA.…”
Section: Inconsistencies In the Use Of Dangerous Pesticides In Mexicomentioning
confidence: 99%
See 1 more Smart Citation
“…We found that nearly all MSFWs reported working in extreme heat, most had core body temperatures reaching and exceeding 38 °C at some point during the workday, and all workers were dehydrated to some degree ( Wagoner et al, 2020 ). Also, many had high levels of organophosphate (OPs), pyrethroids (PYRs), and imidacloprid biomarkers in their urine; the highest pesticide levels were found during the summer, late in the harvest season ( Lopez-Galvez et al, 2018 ; López-Gálvez et al, 2020 ). Although the MSFWs are exposed to occupational risk factors such as heat and pesticides, to our knowledge, no studies have comprehensively examined, longitudinally, the potential effect of these combined occupational factors on kidney function in MSFWs.…”
Section: Introductionmentioning
confidence: 99%